Health-Seeking Behavior of Diabetic and Hypertensive Patients in Rural Communities of Ghana - Michael Amponsah Kodom (Adventist University of Africa, 2022)
Background: This study examined the health-seeking behaviors of patients with diabetes and hypertension in rural communities in Ghana. In Ghana, most studies on diabetes and hypertension are clinically oriented. However, medical-sociological truism suggests that attitudes towards health and illnesses, such as hypertension and diabetes, have a social-cultural perspective. Method: This study adopted a qualitative approach where twenty (20) participants who were either diabetic, hypertensive, or both were interviewed. Results: One of the study's significant findings was that diabetics/hypertensives use only orthodox hospitals to treat their conditions. Another finding was that the problems and challenges diabetics and hypertensives face include financial difficulties, social isolation, and stigmatization. Conclusion: Recommendations were made based on these findings. For instance, the registered traditional medicine practitioners should collaborate with the Ghana Health Service to intensify education on the importance of using certified traditional medicines in the treatment and management of diabetes and hypertension and provide customer-age-factor services at the various health facilities for persons with chronic diseases such as diabetics and hypertension.